Valorisation of the Effect of Waste Aluminum Sawdust on Concrete: Durability Characteristics and Environmental Impacts - Demir, Tuba; Demirel, Bahar; Öztürk, Melek (My University, 2024)
The aim of this study is to examine the effect of replacing waste aluminum sawdust (AS) with fine aggregate on the strength and durability properties of concrete. For this, concrete mixtures with a cement dosage of 400 kg/m3, water/cement (W/C) ratio of 0.40-0.50-0.60 were prepared. Aluminum sawdust obtained from Elazığ industrial site was added to the concrete mixtures by replacing 0%, 0.5% and 1% fine aggregate by volume. After curing in the curing pool for 28 days, the produced concrete samples were placed in the carbonation tank and exposed to the accelerated carbonation test in three different time periods as the 1st, 3rd and 7th days. Tests of compressive strength, splitting tensile strength, ultrasound transmission velocity, porosity and carbonation depth were performed on concrete samples before and after carbonation. The samples that were exposed to carbonation were compared with the samples that did not undergo carbonation. In addition, the microstructure of AS concrete was investigated using scanning electron microscopic images (SEM). In the microscopic images, larger cracks, openings and interfacial voids were observed in the concrete matrix with the addition of AS. However, due to the formation of ettringite in these gaps and cracks after carbonation, the cavities became smaller. As a result of the experiments, it was observed that the optimum W/C ratio was 40% and the AS amount was 0.5% in the use of AS in concrete. In addition, it was found that the carbonation effect improves the compressive and splitting tensile strength and increases the ultrasound transmission rate. Finally, life cycle assessment (LCA) was conducted to evaluate the environmental impacts of the prepared concrete samples. Considering the large amount of natural aggregate consumption, it is thought that the use of waste materials in concrete will provide environmental and economic benefits.
Keywords: Life cycle assessment; Carbonation; Aluminium sawdust; Hardened properties; Microscopic image